Evaluation of performance in receiving heifers fed different sources of dietary lipid - Farran, T.B.; LaBrune, H.J.; Montgomery, Sean P.; Sindt, J.J.; Coetzer, C.M.; Hunter, R.D.; Higgins, James J.; Drouillard, James S.; Blasi, Dale A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two 35-day receiving experiments were conducted using 668 highly stressed crossbred beef heifers to evaluate differences in growth performance, morbidity, and mortality when fed diets containing differing sources of dietary lipid. Heifers received diets containing beef tallow, tallow enriched with a microalgae product containing a high proportion of docosahexaenoic acid (an omega-3 fatty acid), full-fat soybeans, or ground flaxseed. All diets contained approximately 60% concentrate and 40% roughage (alfalfa hay). Feed intake, daily gain, and feed efficiency were poorer (P<0.05) for cattle fed full-fat soybeans than for those fed the other treatments. Feed intake tended to be reduced when micro-algae was top-dressed to the diet, but gain was not negatively impacted. In Trial 2, feed efficiency was improved by the micro-algae. No notable differences among treatments were evident in the percentage of cattle treated for bovine respiratory disease, but cattle fed flaxseed tended to respond better to therapeutic treatments, requiring fewer retreatments.
Keywords: Beef; Receiving cattle; Dietary lipid